ORGANIZATIONAL STRUCTURE DESIGN OF CONTROLLING INVESTMЕNT AND INNOVATION PROCESSES IN THE SUBJECTS OF SMALL ENTREPRENEURSHIP - Anatolievich Doroshenko, Yuri; Vladimirovna Somina, Irina; Vladimirovna Yarmolenko, Irina; Viktorovich Afanasiev, Ilia; Leonidovich Kurbatov, Vladimir (Journal of Applied Engineering Science, 2015)
The paper investigated the possibilities of using the traditional organizational structures of economic entities for solving the functional issues of investment and innovation. It was revealed that the greatest challenges of innovation and investment processes in small enterprises, corresponds matrix structure that allows use of the potential owners, managers and employees of small enterprises, which can act in one person, within not one but several innovative and investment projects. It is proved that the formation of matrix organizational structures in small enterprises should be carried out in the direction of selection and subordination linear functional elements and design of organizational structures, establishment of a mechanism of dual subordination on the basis of bilateral ties and orientation to minimize risks and ensure the best innovative features of the investees. To modify the basic linear structures investment management innovation in the subjects of small business prompted the creation of micro focus groups among owner-managers of small companies and key line departments.